Exploitation in Angela Carter's The Nights at the Circus: An Ecofeminism Study - Honey Cahyono, Helga; Suryani, Suci (University of Brawijaya, 2024)
Exploitation remains a pressing issue today, particularly affecting women, who are often treated as objects of violence and subjected to various forms of exploitation. This phenomenon is also depicted in the character of Fevvers, the female protagonist in Nights at the Circus by Angela Carter, who is portrayed as a half-swan woman enduring exploitation. The aim of this study is to analyze the types of exploitation experienced by the protagonist in the novel. Utilizing qualitative research methods, the study involved data collection and analysis from the text, which included refining and organizing relevant information. The findings reveal that the protagonist has been subjected to exploitation since her adolescence. This underscores how Nights at the Circus not only mirrors the real-world exploitation of women but also highlights its presence in fictional narratives.